MENINGKATKAN KEMATANGAN KARIR REMAJA MELALUI BIMBINGAN KARIR BERBASIS LIFE SKILLS - Lestari, Indah (Universitas Muria Kudus, 2017)
Adolescence is a very important phase in the life cycle of individual development, because lead to a healthy adulthood. This period shows clearly the nature of the transition from the status of childhood to adulthood. Many of the problems that arise at this stage, one problem kesipana career. This becomes a logical consequence of the development of adolescents where there are demands for those preparing for a career. Career problems that occur in adolescents is usually associated with the choice of education, which leads to the selection of the type of work in the future, this problem is very important to note in relation to the number of kebinggungan experienced by adolescents in determining the course of his career,To meet the career needs teenagers, needs to be done pemdampingan intensively from professionals such as counselors in the provision of guidance and counseling services, the needs assessment needs to be linked to the demands of the present, the main curriculum pendiidkan based life skills (life skills), which has become a fundamental issue teenagers, It is necessary for life skills-based career guidance in an effort to improve career kematanga teenagers.